Acupuncture treatment of a pregnant patient with Bell's palsy in the third trimester: Case report - Lan, Danchun; Deng, Wenfei; He, Kunze; Li, Qian; Peng, Xin; Lao, Jinxiong; Li, Ziyong (Frontiers in Neurology, 2023)
Currently, the optimal treatment for Bell’s palsy remains controversial, the combination of corticosteroids and antiviral medications is usually recommended in the early stage. However, treatment is often delayed because the effects of these drugs on pregnant women and fetuses remain unclear. Acupuncture as a safe and effective complementary alternative therapy can alleviate Bell’s palsy symptoms and ameliorate the quality of life. In this case, a 27-year-old female patient who was 26-week pregnant had Bell’s palsy. After five courses of treatment, the patient had recovered.